A river runs through it, and other stories - Maclean, Norman (Chicago University of Chicago Press, 1976)
From its first magnificent sentence, "In our family, there was no clear line between religion and fly fishing", to the last, "I am haunted by waters", A River Runs Through It is an American classic.

Based on Norman Maclean's childhood experiences, the title novella has established itself as one of the most moving stories of our time; it captivates readers with vivid descriptions of life along Montana's Big Blackfoot River and its near magical blend of fly fishing with the troubling affections of the heart.

The paperback edition is now available with an evocative new cover by acclaimed Montana painter Russell Chatham.

"A masterpiece. . . . This is more than stunning fiction: It is a lyric record of a time and a life, shining with Maclean's special gift for calling the reader's attention to arts of all kinds--the arts that work in nature, in personality, in social intercourse, in fly-fishing."--Kenneth M. Pierce, Village Voice

Norman Maclean (1902-90), woodsman, scholar, teacher, and storyteller, grew up in the Western Rocky Mountains of Montana and worked for many years in logging camps and for the United States Forestry Service before beginning his academic career. He retired from the University of Chicago in 1973.
A river runs through it.--Logging and pimping and ''Your pal, Jim.''--USFS 1919
Keywords: Outdoor recreation - Fiction; Fathers and sons - Fiction; Fly fishing - Fiction; Brothers - Fiction; Montana - Social life and customs - Fiction; Domestic fiction; Fishing stories